Distinct and Shared Molecular Mechanisms in Pediatric Antrochoanal Polyps and Chronic Rhinosinusitis with Nasal Polyps: A Proteomic and Metabolomic Integrative Analysis - Chen YC; Wang X; Pan YW; Teng YS; Pan HG (Journal of Inflammation Research)
Yong-Chao Chen, Xin Wang, Yan-Wen Pan, Yi-Shu Teng, Hong-Guang Pan Department of Otorhinolaryngology, Shenzhen Children’s Hospital, Shenzhen, Guangdong, People’s Republic of ChinaCorrespondence: Hong-Guang Pan, Department of Otorhinolaryngology, Shenzhen Children’s Hospital, 7019 Yitian Road, Futian District, Shenzhen, Guangdong, 518038, People’s Republic of China, Tel +86-18938691502, Email 1481717890@qq.comPurpose: The underlying mechanisms of pediatric antrochoanal polyps (ACP)and chronic rhinosinusitis with nasal polyps (CRSwNP) remain largely unexplored. This study investigates their proteomic and metabolomic profiles to uncover unique and overlapping pathways, shedding light on their underlying causes.Methods: Specimens were collected from six children with ACP, six with CRSwNP, and six with normal inferior turbinate mucosa (CK) at Shenzhen Children’s Hospital. Protein profiles were analyzed using data-independent acquisition (DIA) mass spectrometry, while metabolite profiles were assessed via non-targeted metabolomics (UPLC-MS/MS). Differences in proteins and metabolites were identified through statistical selection and bioinformatics, followed by integrated pathway analysis to explore their roles in disease processes.Results: Proteomic analysis identified 1000 differentially expressed proteins (DEPs) in ACP and 880 in CRSwNP compared to controls. Key DEPs in ACP included PEX1 and LYPD2, while CRSwNP included PEX1, CFAP52, SPAG6 and DHRS9. Metabolomic analysis identified 129 differential metabolites in ACP and 11 in CRSwNP, with 5-HTP showing opposite regulation between the two conditions. Pathway analysis pointed to oxidative stress and lipid metabolism disruptions in ACP, and immune and ciliary dysfunction in CRSwNP. Both conditions shared inflammation and extracellular matrix remodeling, but tryptophan metabolism diverged, with 5-HTP reduced in ACP and elevated in CRSwNP.Conclusion: This study highlights oxidative stress and lipid dysregulation as hallmarks of pediatric ACP, distinct from ciliary and immune dysfunction in CRSwNP, with inflammation and matrix remodeling as common features. The opposing regulation of 5-HTP reflects differences in tryptophan metabolism. Key molecules like PEX1, LYPD2, CFAP52, and 5-HTP emerge as potential biomarkers, offering promise for improved diagnosis and targeted therapies in nasal polyp-related conditions, but the small sample size and exploratory design require validation in larger cohorts to ensure clinical applicability.Keywords: maxillary sinus retro polyps, nasal polyps, proteomics, metabolomics, combined analysis, pediatrics